Szczególne definicje strony postępowania w Prawie budowlanym - Prusik-Serbinowski, Filip (Studia Prawa Publicznego, 2026)
According to the provisions of the Code of Administrative Procedure, legal interest constitutes the basis for procedural standing in administrative proceedings. The characteristics of this concept and tool make it a suitable benchmark for determining the subjective scope of most administrative proceedings. When applying this criterion, any entity whose rights and obligations may be affected by the decision concluding the proceedings will be considered a party to the proceedings; conversely, no entity whose legal situation is unaffected by the outcome of the proceedings shall have standing. However, there are certain categories of cases in which the legislator finds it necessary to modify that scope, most often by narrowing it. An example would be in order to expedite the proceedings. This occurs through special provisions that introduce a basis for standing different from the legal interest. Such provisions can be found in Construction Law, among other legislation. This article analyses and assesses those provisions, including an examination of the interpretative doubts arising in the case law of administrative courts and an attempt to resolve these issues. The analysis covers three provisions, each of which modifies the subjective scope of proceedings in a different way to that determined on the basis of the criterion of legal interest. It is possible to distinguish between clarification or direct regulation of the same group of parties that would result from the provisions of the Code, its narrowing, and categorical restriction to only one entity. Each of these regulations should be assessed in terms of precision, legitimacy, purposefulness, and functioning in judicial practice.